Reasons and treatment strategy for discontinuation of dapoxetine treatment in premature ejaculation patients in China: A retrospective observational study. (24th March 2022) - Zhong, Chongfu; Li, Chunlei; Geng, Qiang; Han, Qiang; Gao, Qinghe; Zhang, Jiwei; Wang, Fu; Guo, Jun
Abstract: To assess dapoxetine discontinuation rates and the reasons for discontinuation in Chinese men with premature ejaculation (PE). Information on 906 PE outpatients was obtained from the hospital information system (HIS) in 2019. Of these, 150 patients were chosen. We analysed the dapoxetine discontinuation rate and the reasons for discontinuation over a 12‐week follow‐up period. The mean age of all patients was 33.6 years (range = 18–55), the mean PE duration was 12.36 ± 9.45 months. The 5‐item International Index of Erectile Function (IIEF‐5) score was 21.51 ± 3.80. A total of 37.3% of all the patients remained on the treatment until the 12th week. The cumulative discontinuation rates at the 4th, 8th and 12th weeks were 12%, 41.3% and 62.7%, respectively. The discontinuation rates for all the patients in weeks 0–4, weeks 4–8 and weeks 8–12 were 19.1%, 46.8% and 34.0%, respectively. After 4 weeks, the discontinuation rates dropped sharply. The reasons for patients' discontinuation were as follows: overexpectation of efficacy (30.9%), relapsing after drug withdrawal (26.6%), high cost (25.5%), side effects (9.6%), fear of drug addiction (4.3%), failure of follow‐up (2.1%) and choosing other treatments (1.1%). The dapoxetine treatment discontinuation rate was very high. The main reasons for discontinuation were overexpectation of efficacy and high cost.